Structural characterization and Hirshfeld surface analysis of a CoII complex with imidazo[1,2-a]pyridine - Saikat Kumar Seth (Acta Crystallographica Section E: Crystallographic Communications, 2018)
A new mononuclear tetrahedral CoII complex, dichloridobis(imidazo[1,2-a]pyridine-κN1)cobalt(II), [CoCl2(C7H6N2)2], has been synthesized using a bioactive imidazopyridine ligand. X-ray crystallography reveals that the solid-state structure of the title complex exhibits both C—H...Cl and π–π stacking interactions in building supramolecular assemblies. Indeed, the molecules are linked by C—H...Cl interactions into a two-dimensional framework, with finite zero-dimensional dimeric units as building blocks, whereas π–π stacking plays a crucial role in building a supramolecular layered network. An exhaustive investigation of the diverse intermolecular interactions via Hirshfeld surface analysis enables contributions to the crystal packing of the title complex to be quantified. The fingerprint plots associated with the Hirshfeld surface clearly display each significant interaction involved in the structure, by quantifying them in an effective visual manner.